Protective Role of Melatonin in Neonatal Diseases. (19th November 2013) - Gitto, Eloisa; Marseglia, Lucia; Manti, Sara; D'Angelo, Gabriella; Barberi, Ignazio; Salpietro, Carmelo; Reiter, Russel J.
Abstract : Oxidative stress contributes to the severity of several newborn conditions to the extent that Saugstad coined the phrase "oxygen radical diseases of neonatology." In order to counteract free radicals damage many strategies to augment antioxidant status in ill-term and preterm infants have been proposed and several medications have been experimented with mixed results. Several studies have tested the efficacy of melatonin to counteract oxidative damage in diseases of newborns such as chronic lung disease, perinatal brain injury, necrotizing enterocolitis, and retinopathy of prematurity, giving promising results. The peculiar perinatal susceptibility to oxidative stress indicates that prophylactic use of antioxidants as melatonin could help to prevent or at least reduce oxidative stress related diseases in newborns. However, more studies are needed to confirm these beneficial effects.